The effect of active diuretic therapy on the sodium balance in patients with acute decompensation of chronic heart failure - Vladimir V. Davydov; Ekaterina L. Arehina (ZAO "Consilium Medicum", 2022)
Background. Active dehydration of patients with acute decompensation of chronic heart failure (АDCHF) was often accompanied by the development of hyponatremia. This increased the time of hospitalization and worsened the prognosis. The complication was associated with the side effects of furosemide. Aim. To compare the effect of dehydration and the state of sodium balance after using different methods of parenteral administration of furosemide at an early stage of treatment of АDCHF. Materials and methods. Patients with АDCHF (n=125) were divided into two groups. Group 1 received furosemide as bolus injections, group 2 as an extended intravenous infusion. The process of dehydration was controlled by the amount of urine and body weight loss per day. The effect was considered satisfactory if the body weight decreased by 1.02.0 kg per day. The plasma sodium level was studied on 1, 5, 10 days. Results. In group 2, the satisfactory effect of dehydration was observed 1.7 times more often than in group 1 (p0.05). In group 2 patients on the 5th day of therapy, the number of cases of hyponatremia was 2.3 times less (p0.05). Hyponatremia developed little in patients with a satisfactory effect of dehydration. On the 10th day, the number of cases of hyponatremia in the groups did not significantly differ. Conclusion. Prolonged intravenous infusion of furosemide allowed more control of the dehydration process and the plasma sodium level at an early stage of therapy in patients with АDCHF.